(untitled) (Ágora de Heterodoxias, 2020)
Cultural identity establishes characteristic features, which carry the action of recognizing social customs. Therefore, it must be taken into account that cultural heritage goes beyond traditions because, over time, society may not feel identified with the traditions due and attributed to the inclusion of new cultures, in this case, the gastronomic ones. This article presents the results related to the guidelines formulated for the safeguarding of the intangible cultural heritage, represented by the indigenous cuisine of Bogotá, to carry out a possible conservation of gastronomic memory and the affective relationship towards the immaterial elements representative of cultural identity in Bogotá. In the development of this research, the categories of cultural heritage, intangible heritage, gastronomy, cultural assets will be worked under a mixed approach with a type of descriptive documentary research, taking into account the technique of documentary analysis through analytical matrices. We concluded that it is necessary to continue developing research to protect the gastronomic heritage and contribute to maintaining traditions.